Tracking the cargo of extracellular symbionts into host tissues with correlated electron microscopy and nanoscale secondary ion mass spectrometry imaging. (17th March 2020) - Cohen, Stephanie K.; Aschtgen, Marie‐Stéphanie; Lynch, Jonathan B.; Koehler, Sabrina; Chen, Fangmin; Escrig, Stéphane; Daraspe, Jean; Ruby, Edward G.; Meibom, Anders; McFall‐Ngai, Margaret
Abstract: Extracellular bacterial symbionts communicate biochemically with their hosts to establish niches that foster the partnership. Using quantitative ion microprobe isotopic imaging (nanoscale secondary ion mass spectrometry [NanoSIMS]), we surveyed localization of 15 N‐labelled molecules produced by the bacterium Vibrio fischeri within the cells of the symbiotic organ of its host, the Hawaiian bobtail squid, and compared that with either labelled non‐specific species or amino acids . In all cases, two areas of the organ's epithelia were significantly more 15 N enriched: (a) surface ciliated cells, where environmental symbionts are recruited, and (b) the organ's crypts, where the symbiont population resides in the host. Label enrichment in all cases was strongest inside host cell nuclei, preferentially in the euchromatin regions and the nucleoli. This permissiveness demonstrated that uptake of biomolecules is a general mechanism of the epithelia, but the specific responses to V. fischeri cells recruited to the organ's surface are due to some property exclusive to this species. Similarly, in the organ's deeper crypts, the host responds to common bacterial products that only the specific symbiont can present in that location. The application of NanoSIMS allows the discovery of such distinct modes of downstream signalling dependent on location within the host and provides a unique opportunity to study the microbiogeographical patterns of symbiotic dialogue.